Bioethics, children, and the environment. (5th September 2017) - Murphy, Timothy F.
Abstract: Queer perspectives have typically emerged from sexual minorities as a way of repudiating flawed views of sexuality, mischaracterized relationships, and objectionable social treatment of people with atypical sexuality or gender expression. In this vein, one commentator offers a queer critique of the conceptualization of children in regard to their value for people's identities and relationships. According to this account, children are morally problematic given the values that make them desirable, their displacement of other beings and things entitled to moral protection, not to mention the damaging environmental effects that follow in the wake of population growth. Objectionable views of children are said even to have colonized the view of lesbian, gay, bisexual, and trans (LGBT) people who – with the enthusiastic endorsement of bioethics – increasingly turn to assisted reproductive treatments to have children. In the face of these outcomes, it is better – according to this account – that people reconsider their interest in children. This account is not, however, ultimately strong enough to override people's interest in having children, relative to the benefits they confer and relative to the benefits conferred on children themselves. It is certainly not strong enough to justify differential treatment of LGBT people in matters of assisted reproductive treatments. Environmental threats in the wake of population growth might be managed in ways other than devaluing children as such. Moreover, this account ultimately damages the interests of LGBT people in matters of access, equity, and children, which outcome is paradoxical, given the origins of queer perspectives as efforts to assert and defend the social interests of sexual and gender minorities.